Chemical Biology Approaches to Genome Editing: Understanding, Controlling, and Delivering Programmable Nucleases - Hu, Johnny H.; Davis, Kevin M.; Liu, David R. (Cell chemical biology, 2016)
Programmable DNA nucleases have provided scientists with the unprecedented ability to probe, regulate, and manipulate the human genome. Zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and the clustered regularly interspaced short palindromic repeat-Cas9 system (CRISPR-Cas9) represent a powerful array of tools that can bind to and cleave a specified DNA sequence. In their canonical forms, these nucleases induce double-strand breaks at a DNA locus of interest that can trigger cellular DNA repair processes that disrupt or replace genes. The fusion of these programmable nucleases with a variety of other protein domains has led to a rapidly growing suite of tools for activating, repressing, visualizing, and modifying loci of interest. Maximizing the usefulness and therapeutic relevance of these tools, however, requires precisely controlling their activity and specificity to minimize potentially toxic side effects arising from off-target activities. This need has motivated the application of chemical biology principles and methods to genome-editing proteins, including the engineering of variants of these proteins with improved or altered specificities, and the development of genetic, chemical, optical, and protein delivery methods that control the activity of these agents in cells. Advancing the capabilities, safety, effectiveness, and therapeutic relevance of genome-engineering proteins will continue to rely on chemical biology strategies that manipulate their activity, specificity, and localization. •Genome-editing proteins must be specific and deliverable to be maximally useful•ZFNs, TALENs, and CRISPR-Cas9 can be improved by applying chemical biology principles•Genome-editing proteins have been engineered to control their activity•New protein and RNA delivery methods have broadened the scope of genome editing When someone writes a history of the genome-editing field, 2015 will be the year to reflect on. In this review, Hu et al. provide an overview of the exploding field and how chemical biology strategies are delivering the tools needed to advance genome editing.